Relação entre os atributos funcionais e características do habitat em comunidades de girinos - Queiroz, Cássia de Souza [UNESP] (2014)
Environmental characteristics and evolutionary history of lineages are factors known to influence species coexistence in a community. The functional traits of species that determine how the species uses resources, along evolution, can differ or remain similar to their ancestors. Abiotic characteristics promote selection of traits that allow survival under a set of environmental conditions. Overcoming the taxonomic level and analyze the communities based on the functions they play in ecological systems can be the key to connect patterns and processes in community ecology. Our goal was to understand way the functional attributes of the larval stage of frogs are related to habitat characteristics, considering the habitat acts as a filter for the occurrence of tadpoles, and the habitat homogenization can limit the composition to those species with certain attributes. We expect then that the gradients of depth and complexity of the vegetation within the water bodies act as filters in the local distribution of morphological and functional traits of the tadpoles. Compiled database of studies with communities of tadpoles developed in areas of semideciduous forest in the State of São Paulo and determine the occurrence of tadpoles of 23 frog species in 41 habitats. We tested the existence of a relationship between eight functional traits of tadpoles with depth and vegetation types within the water bodies in which they occurred. Our results indicate that the association of morphological traits of tadpoles with water bodies was not random, showing that gradients of depth and number of vegetation types influence the distribution of tadpoles in habitats. The depth and number of types of vegetation in water bodies appear to impose a continuum in species distribution, being an extreme represented by species with traits that have better performance in deeper bodies of water with little vegetation types, as nektonic and filter-feeding tadpoles and at the ...